Co-addictive human–machine configurations: Relating critical design and algorithm studies to medical-psychiatric research on “problematic Internet use” - Helm, Paula; Matzner, Tobias (New media & society, 2024)
Next to popular term Internet addiction, problematic Internet use (PIU) has established itself as an umbrella term for all types of repetitive impairing behaviors associated with new media technologies. Yet, debates about categorization, prevention, and treatment are nowhere near settled. When it comes to classification, medical-psychiatric research has so far retained authority. Here, PIU is examined primarily at the level of the individual user, and it is at this level that solutions are sought. Complementing this, research from critical algorithm studies and technology ethics emphasize the design of many applications as problematic, while cautioning against a determinist view of technology making people addicted. Based on new materialist conceptions of responsibility, the article argues for integrating the different perspectives into a relational understanding of co-addictive human–machine configurations. The goal is to capture the interactive character of PIU, and to achieve a well-calibrated distribution of responsibilities in avoiding destructive habits.